County's giveaway draws business, boosts economy. - Kalomiris, Paul (American City & County, 2000)
Calvert County, Maryland, offered free land in its industrial park to attract business. Developed in the mid-1970s, the industrial park had 16 vacant lots in the summer of 1997. To qualify for free land companies had to be involved in high-technology businesses, such as computer programming or software development. Ten-year notes were signed by the companies, which would be forgiven if a number of criteria had been met, such as a new facility had been constructed within 2 years or an agreed-upon number of workers had been hired. If the goals were not met the note would become due. The number of vacant lots has dropped to 3, and the incentive program has been discontinued.